Software modernization to embrace quantum technology. (January 2021) - Pérez-Castillo, Ricardo; Serrano, Manuel A.; Piattini, Mario
Highlights: Quantum computing is today more mature and many of their application are today real. Classical information systems will not be throw away in a short-term period. Reengineering of classical-quantum system is needed to preserve business knowledge. Quantum knowledge can be represented with extensions of KDM and UML. KDM and UML makes reengineering systematic and technologically-agnostic. Abstract: Quantum Computing is becoming an increasingly mature area, with a simultaneous escalation of investment in many sectors. Quantum technology will revolutionize all the engineering fields. For example, companies will need to add quantum computing progressively to some or all of their daily operations. It is clear that all existing classical information systems cannot be done away with. Rather than that occurring, it is expected that some quantum algorithms will be added, so that they can work alongside classical information systems. There has been no systematic solution offered to deal with this challenge so far. This research proposes a software modernization approach (model-driven reengineering) designed to restructure classical systems to work in conjunction with quantum systems, thereby providing target environments that combine both of these computational paradigms. The approach proposed is systematic, and based on existing software engineering standards like the Knowledge Discovery Metamodel and the Unified Modelling Language. It could therefore be applied in industry in a way that complies with the existing software evolution processes. The independence of this proposal with respect to quantum programming environments is also guaranteed, making its application feasible in the changing environment in today's quantum industry. The main implication of this approach is technical, but also economic, since it enables the reuse of the knowledge embedded in legacy systems, while at the same time the new quantum-based projects are speeded up.